Benefits and Safety of Empiric Antibiotic Treatment Active Against KPC-Producing Klebsiella pneumoniae for Febrile Neutropenic Episodes in Colonized Children with Acute Leukemia—An 8-Year Retrospective Observational Study - Alessandra Micozzi; Cristina Luise; Chiara Lisi; Luisa Moleti; Stefania Santilli; Giuseppe Gentile (Antibiotics)
In children with acute leukemia (AL), the mortality rate from Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae bloodstream infection (KPC-KpBSI) exceeds 50%, highest when active treatment is delayed. Neutropenic KPC-K. pneumoniae carriers are at high risk of KPC-KpBSI, and preemptive empiric antibiotic treatment (EAT) of febrile neutropenic episodes (FNEs) active against KPC-K. pneumoniae may reduce this mortality. We conducted an 8-year (2014–2021) retrospective observational study of 112 febrile neutropenic episodes (FNEs) in 32 children with AL who were KPC-K. pneumoniae carriers: standard EAT for 39 FNEs and active EAT for 73 FNEs (52 ceftazidime/avibactam (CAZAVI)-based and 21 colistin-based combinations, and 5 CAZAVI monotherapy). Successful outcomes (survival from FNE) were observed in 94%; seven were fatal, with four due to infectious causes. KPC-KpBSIs caused 10/112 FNEs, 10/20 g-negative BSIs, and 3 deaths. The mortality rate of KPC-KpBSI was 30%. Active EAT was successful in 97% of the FNEs, compared to 87% with standard EAT. All deaths from KPC-KpBSI occurred in patients who received standard EAT, while none occurred with active EAT. KPC-KpBSI mortality rate with initial inactive treatment was 60%. CAZAVI-based EAT was successful in all FNEs, with a higher success rate without any modification compared to colistin-based EAT, where nephrotoxicity occurred in 14%. Therefore, active EAT, mainly a CAZAVI-based combination, was effective, safe, and associated with low overall and KPC-KpBSI-related mortality.